2005
DOI: 10.1089/acm.2005.11.1085
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Group Aerobic Exercise and T'ai Chi on Functional Outcomes and Quality of Life for Persons Living with Acquired Immunodeficiency Syndrome

Abstract: This study shows that TC and EX improve physiologic parameters, functional outcomes, and QOL. Group intervention provides a socialization context for management of chronic HIV disease. This study supports the need for more research investigating the effect of other types of group exercise for this population. This study sets the stage for a larger randomized controlled trial to examine the potential short- and long-term effects of group exercise that may prove beneficial in the management of advanced HIV disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 23 publications
0
90
0
8
Order By: Relevance
“…We found that exercise training increased social interactions and improved psychological well-being in HIV+ men and women with body fat changes. Others have reported both the benefits of exercise training as a source of social support [32] or highlighted the importance of social support in coping with HIV disease [33]. Exercise training may have facilitated social interactions among participants, provided an opportunity for them to share experiences about the impact of body fat changes, and helped them regain a measure of control over disclosure of their health status.…”
Section: Discussionmentioning
confidence: 99%
“…We found that exercise training increased social interactions and improved psychological well-being in HIV+ men and women with body fat changes. Others have reported both the benefits of exercise training as a source of social support [32] or highlighted the importance of social support in coping with HIV disease [33]. Exercise training may have facilitated social interactions among participants, provided an opportunity for them to share experiences about the impact of body fat changes, and helped them regain a measure of control over disclosure of their health status.…”
Section: Discussionmentioning
confidence: 99%
“…As investigações sobre exercício físico com os indivíduos infectados pelo HIV têm enfatizado fatores de estudo isolados como, por exemplo, o treinamento aeróbio (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) ou muscular, com avaliação através do teste de uma repetição máxima (1-RM) ou o treinamento com séries múltiplas, que conforme Carpinelli e Otto (32) , é a execução de, no mí-nimo, três séries para cada exercício (26,(33)(34)(35)(36)(37)(38)(39)(40) . Considerando o treinamento concorrente, ou seja, a associação dos componentes aeróbio e força na mesma sessão de treinamento (41,42) , existe uma carência de estudos sobre a sua viabilidade terapêutica nos principais parâmetros clínicos (imunológico e virológico) e de aptidão física relacionada com a saúde (cardiorrespiratório e muscular).…”
Section: Introductionunclassified
“…O exercício físico contribui de maneira eficaz na redução da ansiedade, depressão e na melhora do bem-estar e qualidade de vida em indivíduos saudáveis (4) . Sendo assim, diversos estudos têm evidenciado tais benefícios em indivíduos infectados pelo vírus HIV (20,22,39) . Neidig et al (22) realizaram um estudo durante 12 semanas e evidenciaram melhora significativa nos índices de sintomas associados à depressão avaliados através do CES-D (Centers for Epidemiological Studies -Escala de Depressão) e na subescala depressão/rejeição avaliada através do POMS (Profile of Mood States).…”
Section: Efeitos Do Exercício Nos Fatores Psicológicosunclassified
“…Galantino et al (39) evidenciaram diferença significativa na subescala saúde, avaliada através do Medical Outcomes Short Form (MOS-HIV), tanto no grupo exercício moderado quanto no de tai chi. Outros autores (20) também encontraram melhora significativa no status saúde total e função cognitiva, avaliadas através do Medical Outcomes Study HIV Health Survey, durante 24 semanas.…”
Section: Efeitos Do Exercício Nos Fatores Psicológicosunclassified